Reducing the cesarean delivery rate. (July 2021) - Levine, Elliot M.; Delfinado, Leah N.; Locher, Stephen; Ginsberg, Norman A.
Abstract: Background: The cesarean delivery rate has been rising in recent years, having associated maternal morbidities. Elective induction of labor has also been seen to rise during this same time period. Objective: This current study investigated the difference in the cesarean delivery rate between induction of labor and spontaneous labor among nulliparous, term, singleton, and vertex-presenting women. Study Design: A retrospective cohort in a single institution over a seven-year period was used for this analysis, observing the difference in cesarean delivery rate at different term gestational ages and neonatal morbidity using the 5-minute Apgar score < 5. Results: A statistically significant difference was found in cesarean delivery rate between those women whose labor was induced and those whose labor began spontaneously, at each term gestational age of labor initiation (P < 0.001). The proportion of indications for induction was described (i.e. elective vs. medically-indicated), and no difference was found for neonatal morbidity between the groups analyzed, using the 5-minute Apgar score as the perinatal outcome measure. Conclusion: A comparison was made between spontaneous and induced labor regarding the resultant cesarean delivery rate, and a significant difference was found favoring spontaneous labor. This should be considered when electing to deliver using an induction methodology for nulliparous women, especially when there are no medical indications for it.